Dietary pomegranate pulp to improve meat fatty acid composition in lambs - Natalello A.; Luciano G.; Morbidini L.; Priolo A.; Biondi L.; Pauselli M.; Lanza M.; Valenti B. (Innovation for sustainability in sheep and goats, 2019)
The aim of this study was to evaluate the effect of dietary pomegranate pulp (PP) on the intramuscular fatty acid (FA) composition in lambs. Seventeen Comisana lambs were individually stalled, divided into two groups and fed for 44 days: a barley-corn based concentrate diet (CON-8 lambs) or a concentrate diet containing 20% of PP to partially replace barley and corn (POM-9 lambs). The inclusion of PP in the diet produced an overall improvement of the fatty acid composition of LTL. In particular, percentages of C18:1 t11 (0.73 vs 1.38, P < 0.001), C18:2 c9t11 (0.35 vs 0.94, P < 0.001), C18:3 c9c12c15 (0.37 vs 0.51, P < 0.001) and C18:2 c9c12 (5.37 vs 7.09, P = 0.035) were higher in the meat of POM group in comparison with CON lambs. All the mentioned FAs are involved in the ruminal metabolism of lipids, suggesting an effect of the bioactive compounds contained in PP on the FA biohydrogenation. In addition, C18:3 c9t11c13 (punicic acid), the peculiar FA of pomegranate seeds, was detected only in the muscle of POM lambs, representing 0.48% of the total fatty acids. The percentage of PUFA was significantly higher in meat from POM group compared to CON. In conclusion, a diet containing 20% of PP increased the proportion of healthy fatty acids in meat without compromising animal growth.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)